2018
DOI: 10.1371/journal.pone.0191401
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic cup position following posterior and lateral approach to total hip arthroplasty. An explorative randomized controlled trial

Abstract: The two most common surgical approaches to total hip arthroplasty are the posterior approach and lateral approach. The surgical approach may influence cup positioning and restoration of the offset, which may affect the biomechanical properties of the hip joint.The primary aim was to compare cup position between posterior approach and lateral approach. Secondary aims were to compare femoral offset, abductor moment arm and leg length discrepancy between the two approaches. Eighty patients with primary hip osteoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“… 13 Moon et al 14 compared two techniques of posterior soft tissue repair in 167 hips (150 patients) at a 28-month follow-up and reported better outcomes and less dislocations with trans-osseous repair compared with gluteus medius/short rotators tendon-to-tendon repair. Finally, Kruse et al 16 compared radiographic outcomes of posterior and lateral approaches in 80 patients and reported that the femoral offset and abductor moment arm were significantly increased when using posterior compared with lateral approach.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Moon et al 14 compared two techniques of posterior soft tissue repair in 167 hips (150 patients) at a 28-month follow-up and reported better outcomes and less dislocations with trans-osseous repair compared with gluteus medius/short rotators tendon-to-tendon repair. Finally, Kruse et al 16 compared radiographic outcomes of posterior and lateral approaches in 80 patients and reported that the femoral offset and abductor moment arm were significantly increased when using posterior compared with lateral approach.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in LLD were calculated for the final analysis. Previous studies already showed good to excellent intraobserver and interobserver variation using the same measurements with this software [38]. However, we also assessed the interobserver variability for all outcomes.…”
Section: Radiographic Measurementsmentioning
confidence: 95%
“…11 Kruse et al compared radiographic outcomes of posterior and lateral approaches in 80 patients and reported that the femoral offset and abductor moment arm were significantly increased when using a posterior compared with a lateral approach. 12 Moon et al compared two techniques of posterior soft tissue repair in 167 hips (150 patients) at 28 months follow-up and reported better outcomes and fewer dislocations with a transosseous repair compared with gluteus medius/short rotators tendonto-tendon repair 13 (►Table 2).…”
Section: Rcts With Significant Findingsmentioning
confidence: 99%